Tumor cell dissemination to the bone marrow and blood is associated with poor outcome in patients with metastatic breast cancer - Hartkopf, Andreas; Stefanescu, Diana; Wallwiener, Markus; Hahn, Markus; Becker, Sven; Solomayer, Erich-Franz; Fehm, Tanja N.; Brucker, Sara Y.; Taran, Florin-Andrei (Breast cancer research and treatment, 2014)
The purpose of this study was to assess the impact of disseminated tumor cells (DTCs) on progression-free and overall survival (OS) in patients with metastatic breast cancer (MBC) and to compare it to simultaneous detection of circulating tumor cells (CTCs) from the blood in a subgroup. Disseminated tumor cells were identified in bone marrow (BM) aspirates by immunocytochemistry (pancytokeratin antibody A45-B/B3) and cytomorphology prior to the beginning of a new-line therapy. CTCs were enumerated by the CellSearch® technology. BM was obtained from 178 patients with MBC; 64/178 (36 %) patients were DTC-positive. Disseminated tumor cells occurred more frequently in patients with visceral metastases (p = 0.020) and ≥2 lines of therapy (p = 0.017). CTCs were assessed in 33 of these patients and 17/33 (52 %) patients had CTC counts ≥5 CTCs/7.5 ml blood. There was no significant association between the DTC and CTC status. Univariate analysis revealed DTC detection as a significant predictor of poor OS (p < 0.001); median OS in DTC-negative versus DTC-positive patients was 52 [95 % confidence interval (CI) 38-67] versus 28 [95 % CI 19-37] months. Moreover, as described previously, patients with ≥5 CTCs/7.5 ml blood were at an increased risk of disease progression (p = 0.026) and death (p = 0.025). Disseminated tumor cells are predictors of poor prognosis in MBC, highlighting the role of tumor cell dissemination into the BM for breast cancer progression. The absence of a significant association between concurrent DTCs and CTCs suggests they might represent different aspects of systemic BC spread.